2017
DOI: 10.1071/sh16177
|View full text |Cite
|
Sign up to set email alerts
|

Ten years on: a review of medical terminations of pregnancy performed in a sexual health clinic

Abstract: The initial provision of MToP through CSHS was anticipated to be a short-term arrangement; however, 10 years on, this service continues with strong community demand. Provision of MToP services through primary healthcare settings can help improve access for women living outside of major metropolitan areas. If moves to decriminalise abortion in Queensland are successful, there is potential for even greater access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…The proportion of Aboriginal women accessing FPNT’s EMA service (11%) was approximately the same as the proportion of Aboriginal women resident in the Greater Darwin area (9%) and similar to that reported in a review of EMAs at the Cairns Sexual Health Service 13 . The proportion of women whose usual residence was outside of the Greater Darwin area (ie in Remote Australia or Very Remote Australia) was 15%.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The proportion of Aboriginal women accessing FPNT’s EMA service (11%) was approximately the same as the proportion of Aboriginal women resident in the Greater Darwin area (9%) and similar to that reported in a review of EMAs at the Cairns Sexual Health Service 13 . The proportion of women whose usual residence was outside of the Greater Darwin area (ie in Remote Australia or Very Remote Australia) was 15%.…”
Section: Discussionsupporting
confidence: 71%
“…The proportion of clients with ongoing pregnancy and requiring surgical uterine evacuation were lower than in other reported series in Australia; 13,15,16 however, none of these series reported on the number of clients actively managed with additional doses of miso- We found that presenting for an EMA also provided the opportunity for staff at FPNT to discuss contraception with women and importantly, more than 85% of those seen again were subsequently using more effective contraception after EMA than they were prior to attending the service. The number of long-acting reversible contraceptives may be an underestimate as chart review was performed at four weeks post-EMA and only those inserted by that time were counted.…”
Section: Preparations For Implementation Of Servicecontrasting
confidence: 53%
See 2 more Smart Citations
“…The Cairns Sexual Health Service performs over 400 medical abortions each year and registered nurses carry out the initial evaluation and counselling, along with the follow-up. 4 Prescribing of the MS 2-Step (mifepristone-misoprostol) medication and the consent process are currently done by medical practitioners, although it is expected that nurses will be providing the latter by the end of 2019. Nurses (as opposed to nurse practitioners) in Australia cannot prescribe under the Pharmaceutical Benefits Scheme, but can perform all the other work associated with non-complicated medical abortions.…”
mentioning
confidence: 99%